The estimated dietary and health impact of implementing the recently approved ‘high in’ front-of-package nutrition symbol in Canada: a food substitution scenario modeling study - Flexner, Nadia; Ahmed, Mavra; Mulligan, Christine; Bernstein, Jodi T.; Christoforou, Anthea K.; Lee, Jennifer J.; Khandpur, Neha; L’Abbe, Mary R. (Frontiers in Nutrition, 2023)
Background: Front-of-pack labeling (FOPL) has been identified as a cost-effective policy to promote healthy food environments and to help consumers make healthier food choices. Consumer surveys report that after implementation of mandatory ‘high in’ FOPL symbols between 30% and 70% of consumers choose or were willing to choose products with fewer ‘high in’ symbols. Health Canada has recently published FOPL regulations that will require prepackaged food and beverages that meet or exceed thresholds for sodium, total sugars, or saturated fat to display a ‘high in’ FOPL nutrition symbol. Objectives: The aims were to estimate the potential 1) dietary impact of substituting foods with similar foods that would display at least one less ‘high in’ symbol, and 2) the number of diet-related noncommunicable disease (NCD) deaths that could be averted or delayed due to estimated dietary changes. Methods: Baseline and counterfactual intakes of sodium, total sugars, saturated fats, and energy were estimated among Canadian adults (n=11,992) using both available days of 24h-recall data from the 2015 Canadian Community Health Survey-Nutrition (CCHS). Similar foods to those reported in CCHS that would display at least one less ‘high in’ symbol (n=239) were identified using a Canadian branded food composition database. Based on current FOPL consumer research, identified foods were substituted for 30%, 50%, and 70% of randomly selected CCHS-Nutrition adult participants and for all adult participants. Potential health impacts were estimated using the Preventable Risk Integrated ModEl. Results: Mean dietary reductions of between 73 and 259 mg/day of sodium, 2.0 and 6.9 g/day of total sugars, 0.2 and 0.5 g/day of saturated fats, and 14 and 46 kcal/day of energy were estimated. Between 2,148 (95% CI 1,913-2,386) and 7,047 (95% CI 6,249-7,886) of deaths due to diet-related NCDs, primarily from cardiovascular diseases (70%), could potentially be averted or delayed if Canadians choose products with fewer ‘high in’ symbols. Conclusions: Results suggest that FOPL could significantly reduce sodium and total sugar intakes among Canadian adults, the consequences of which could avert or delay an important number of diet-related NCD deaths. These findings provide relevant data to support the importance of the impending FOPL regulations.